Athena Itonia : geography and meaning of an ancient Greek war goddess - Lalonde, Gerald V., 1938- (Mnemosyne, Supplements;, 2020)
With Athena Itonia: Geography and Meaning of an Ancient Greek War Goddess Gerald V. Lalonde offers the first comprehensive history of the martial cult of Athena Itonia, from its origins in Greek prehistory to its demise in the Roman imperial age. The Itonian goddess appears first among the Thessalians and eventually as the patron deity of their famed cavalry. Archaic poets attest to "Athena, warrior goddess" and her festival games at the Itoneion near Boiotian Koroneia. The cult also came south to Athens, probably with the mounted Thessalian allies of Peisistratos. Hellenistic decrees from Amorgos tell of elaborate festival sacrifices to Athena Itonia, likely supplications for protection of the islanders and their maritime trade when piracy plagued the Cyclades after collapse of the Greek naval forces that policed the Aegean Sea. This will be an indispensable volume for all interested in the social, political, and military uses of ancient Greek religious cult and the geography, chronology, and circumstances of its propagation among Greek poleis and federations.